Effects of garnet particles and chill casting conditions on properties of aluminum matrix hybrid composites - Naeem, Haider Tawfiq; Abdullah, Firas Fouad (Eclética Química, 2019)
In recent years, the demand of high-performance and light-weight materials was increasing for industrial applications. The present research aims to study microstructural and mechanical properties of aluminum matrix hybrid reinforced 6-12 wt.% of garnet under the effects of materials chill casting during the manufacturing aluminum matrix composite. In this research work, metallic mold and no chills were used. In order to evaluate the quality of the chill end casting microstructure, hardness, and tensile tests were conducted on the prepared composite specimens. Aluminum matrix composites underwent the chill casting process have been examined using the optical microscope, scanning electron microscopy and X-ray diffraction. Microstructure outcomes of the casted Al-composites alloy indicated that having precipitations (Al2Si, AlCuMg2Si) and Garnet particulates hard within the Al-matrix. The results showed that the copper chill casting is the better one in terms of improving the mechanical properties because of its high volumetric heat capacity. Aluminum composite with addition of 9% Garnet composite produced via copper chill casting exhibits better mechanical properties.